Biochemical and molecular characterization of putative immunoprotective molecules of the soft tick, Ornithodoros savignyi Audouin (1827) - Neitz, A.W.H. (Albert Walter Herman) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.